Upaya Birokrasi Pemerintah dalam Mensosialisasikan Covid-19 di Lingkungan Masyarakat - Fatimah, Nurliza; Amelinda F, Lala; Maulana P, Trinadi (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
In December 2019, the world was shocked by the presence of a new virus in Wuhan, one of the cities in China, the Corona Virus or commonly referred to as Covid-19. Covid-19 is a contagious disease and therefore prevention of Covid-19 should be done as soon as possible. The Chinese National Health Commission explains that the coronavirus is easy to spread, Covid-19 can be transmitted from humans to humans who have been infected with Covid-19. Besides Covid-19 can also be attached to items that have been touched by patients who are positive for Covid-19 and are close to Covid-19 patients. The existence of Covid-19 caused panic everywhere - one of them in Indonesia, in dealing with Covid-19, the Indonesian government has provided new policies and appeals to the community to overcome the Covid-19 outbreak. But there are still many people who do not obey the appeal of the government and violate the policies that have been made by the Government. Therefore this study aims to analyze how the efforts of the government bureaucracy in socializing Covid-19 in the community environment. The method used in this study is the method of literature to produce data in the form of descriptive data, words or words from individuals who are observed, then observed, the object of research in the form of the library works in the form of scientific journals, books, mass media articles.